Investigation English Songs To Reduce Speaking Anxiety In Efl Classroom - Cindy Selvia Somantri Putri; Wahyu Satya Gumelar; Andriana Gaffar (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Many students experience anxiety in the EFL classroom; their lack of fear and sense of confidence when speaking English in class causes them to dislike the language and even not want to attend English classes. Researchers looked at learning songs in the classroom and found that students were more relaxed and comfortable singing the songs because they could express what they liked about them, choose songs based on genre, enjoy, each one hear the words pronounced correctly, understand the meaning and fee that the classroom environment was more exciting than when they were learning to speak. A qualitative approach using a phenomenological research methodology is used. Techniques for gathering data include interviews, questioners, and observation. Analyzing data from questionnaires to earn about students’ responses to English songs and speaking, interviews to obtain precise findings indicating english songs classes are highly beneficial and can lessen speaking fear in the classroom participants from MEKAR ARUM senior high school class XI science. Thirty students completed the questionnaire, and five participants were interviewed. The study’s findings confirm that listening to English songs. Increase students’ reducing when speaking English. Students also report the english songs are highly enganging and can help students feel less nervous in the classroom. The typical characteristics experienced by students who feel golden in speaking English are lack of self-confidence, fear of being laughed at by their friends, anxiety and fear. This is where English songs students fee freedom of expression, freedom to sing loudly, don’t feel